Microbial network stability is linked to soil multifunctionality and functional trade-offs under long-term fertilization in a dryland agroecosystem - Fangfang Li; Xihe Wang; Yaping Huang; Xin Li; Lei Wu; Jinyu Yang; Wanli Xu; Wenju Zhang (Agriculture, Ecosystems & Environment, 2027)

Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Parameterization of dead vegetation effects on dust emission using soil tillage index in an offline meteorology-chemistry model - Ieong-in Kaman Kong; Mizuo Kajino; Yaping Shao; Jing Wu; Kei Kawai; Tsuyoshi Thomas Sekiyama; Takashi Maki; Yasunori Kurosaki; Masahide Ishizuka; Banzragch Nandintsetseg; Masato Shinoda; Batjargal Buyantogtokh; et al. (Aeolian Research, 2026)

Optimizing organic resource allocation to enhance microbial necromass nitrogen accrual: Evidence from multiple long-term fertilization experiments - Jun Wang; Yaping Huang; Qiong Xiao; Dong Wu; Dongchu Li; Xin Li; Lei Wu; Yinghua Duan; Minggang Xu; Wenju Zhang (Agriculture, Ecosystems & Environment, 2026)

A bioinspired self-pumping Janus interface for wet-adhesive epidermal ECG monitoring - Zhiwei Jiang; Yaping You; Hui Zhang; Cihui Liu; Shaohong Wu; Zixiang Li; Songchao Fu; Xia Liu; Yiran Jing; Yuzhen Li; Cheng Chen; Lehao Ren (Chemical Engineering Journal, 2026)

A bone-homing DNA tetrahedral framework nucleic acids nanodevice orchestrates osteogenic regeneration to rescue postmenopausal osteoporosis - Qiumei Li; Fenglin Zhou; Shiyi Zeng; Yue Gao; Qian Shen; Yaping Wu; Chuan Ma; Yunfeng Lin; Jingang Xiao; Kui Huang (Chemical Engineering Journal, 2026)

GLSP ameliorates monocrotaline-induced pulmonary arterial hypertension through inhibition of the PI3K/AKT and MAPK signaling pathways - Yingying Wei; Siying Zuo; Na Deng; Haijun Guo; Liwei You; Yaping Zuo; Yan Wu; Zhangrong Chen; Wei Li; Xiaoyun Si (Journal of Molecular Histology, 2026)

Effective risks and dominant factors of drought-flood abrupt alternation events to global socio-ecological systems - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng; Baisha Weng; Jianzhu Li (Journal of Hydrology, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

Metabolic engineering of Dunaliella salina enhances astaxanthin production: combined effects of heterologous enzyme co-expression and dual-stress optimization - Hao Zhang; Yifan Kong; Yaping Shao; Ziqi Zhang; Celong Zhao; Fuhao Xu; Fenglin Yang; Fengjie Sun; Yulin Cui; Yuyong Wu; Chunxiao Meng; Zhengquan Gao (World Journal of Microbiology and Biotechnology, 2026)

In situ generation of NKG2D CAR T/NK cells via a tumor-targeted lipoplex for enhancing cancer immunotherapy - Xiaoxuan Xu; Wenzhe Yi; Xiangshi Sun; Zhiwen Zhao; Jialin Duan; Ting Wu; Xiaoting Shan; Jie Li; Dangge Wang; Yaping Li (Science Bulletin, 2026)

Loss of foxp3a drives sex-specific immune-metabolic remodeling across the gut-liver-gonad axis in zebrafish - Yuhang Hu; Deinyefa Godfree Igbiriki; Nan Wu; Jialin Li; Junheng Liu; Jiuwu Yin; Jinping Duan; Xianmei Li; Zhixian Qiao; Feng Xiong; Yingyin Cheng; Wanting Zhang; et al. (Fish & Shellfish Immunology, 2026)

Nitrogen limitation enhances Irgarol 1051 toxicity by aggravating PSII photoinhibition in the marine diatom Thalassiosira weissflogii - Yuheng An; Shumin Zeng; Futian Li; Jun Wang; Xuexia Zhu; Juntian Xu; Yaping Wu (Marine Environmental Research, 2026)

Synergistic enhancement of sodium storage in bamboo-derived hard carbon via Ni nanoparticle incorporation and P-doping - Wanquan Liu; Liu Wang; Wenjing Lu; Yong Cheng; Yu Chen; Enze Ren; Zhenyao Wang; Jing Wu; Xinhui Li; Yaping Zeng (Biomass and Bioenergy, 2026)

Large-scale farming enhances soil health in contrast to smallholder management: Insights from a field survey - Xin LI; Dong WU; Yaping HUANG; Xiao YANG; Gilles COLINET; Caroline DE CLERCK; Wenju ZHANG; Minggang XU; Jeroen MEERSMANS (Pedosphere, 2026)

Seawater acidification accelerates growth but hastens decline in batch cultures of the marine diatom Thalassiosira pseudonana - Haiyang Zong; Zihao Sun; Dongmei Lv; Yu Shang; Yaping Wu; Juntian Xu; Futian Li (Marine Environmental Research, 2026)

Promoting the lattice oxygen mechanism via electronic modulation: Cobalt doping and heterointerface effects in RuO2@CuO for enhanced acidic oxygen evolution catalysis - Yuhe Zhang; Yuhui Sun; Yuchen Yang; Yaping Tang; Wei Jiang; Xianyu Chu; Chunbo Liu; jihui Lang; Yuanyuan Wu; Feifan Guo (Chemical Engineering Journal, 2026)

Linear time-lag effects and nonlinear interactions of global drought-flood abrupt alternation in responses to multiple factors - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng; Jianzhu Li (Journal of Hydrology, 2026)

Synthetic pertinence clustering and reinforced evolutionary algorithm for the hybrid E-commerce green location routing problem - Chang Lv; Chaoyong Zhang; Yaping Ren; Leilei Meng; Jianzhao Wu (Swarm and Evolutionary Computation, 2026)

Dynamic hydrogen buffer integrated with single Pt sites for enhanced durability of high-temperature proton exchange membrane fuel cells - Yabin Xu; Jing Tian; Li Wang; Jiuli Xia; Yandong Wu; Qie Liu; Jingjing Wang; Shiqian Du; Tingting Han; Miaoyu Li; Zuyao Jiang; Yaping Gu; et al. (Science Bulletin, 2026)

Genomic insights into recurrent demographic collapses and recovery dynamics in Tibetan antelopes (Pantholops hodgsoni) - Weimin Kuang; Hongfeng Zhang; Yingli Jiang; Han Hu; Wei Huang; Yaping Zhang; Xiaomin Wu; Li Yu (Science China Life Sciences, 2026)

Corrigendum to ‘Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis’ [Aquaculture 578 (2024) 740142] - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2026)

Long-term fertilization-induced increases in glomalin-related soil protein depend on phosphorus input and aggregate stability across climatic zones - Hongbo Yang; Guanmo Li; Dong Wu; Qiong Xiao; Xin Li; Yaping Huang; Jeroen Meersmans; Gilles Colinet; Minggang Xu; Wenju Zhang (Soil and Tillage Research, 2026)

Selective CO2 photoreduction to acetate enabled by charge-enriched interface sites confined in metal nanoclusters - Juncheng Zhu; Yang Wu; Jun Hu; Zijia Lin; Zexun Hu; Mingyu Wu; Runhua Chen; Kai Zheng; Wenxiu Liu; Bangwang Li; Junfa Zhu; Yang Pan; et al. (Science Bulletin, 2026)

Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Spatiotemporal dynamics of microplastics in urban stormwater runoff: Functional area effects and transport pathways (Shanghai, China) - Junhao Li; Bowen Yu; Chengjin Cao; Liuxing Wu; Yaping Zhao; Ruiyun Zhu; Yangyang Hu; Minsheng Huang; Lei Wang; Xinlin Yan (Journal of Contaminant Hydrology, 2026)

Distribution characteristics and controlling factors of Wenchang Formation fan in the Enping 17 Sag steep slope zone, Zhujiang River Mouth Basin - Yaping Sui; Guangrong Peng; Wei Wu; Guangxu Wang; Xiaomeng Wang; Zhendong Feng; Jing Yu; Tao Wan; Weiye Zhao (Acta Oceanologica Sinica, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Triazine herbicides inhibit phytoplankton photosynthesis in the East China Sea: A species-specific assessment - Yaping Wu; Xiangyu Li; Peijian Ding; Huifang Li; Juntian Xu (Marine Environmental Research, 2026)

Zn isotopic composition and variability in large-scale aquatic environment of the Tibetan Plateau: implications for Zn migration and sources - Xiaoli Liu; Zhiwen Dong; Yan Yan; Rui Wu; Lunche Wang; Yaping Shao (Journal of Hydrology, 2026)

Carbonic anhydrase modulates photosynthetic responses to UV radiation in diatoms across temperature gradients - Xiangyu Li; Yuheng An; Juntian Xu; Yaping Wu; John Beardall (Journal of Photochemistry and Photobiology B: Biology, 2026)

Grass carp (Ctenopharyngodon idella) Kat5 mediates P53 acetylation to induce apoptosis and promotes GCRV replication - Bao Liu; Chuxin Wu; Xianggao Meng; Tingting Yu; Xucheng Zhang; Jing Liu; Mingzhi Li; Yaping Weng; Huiling Mao; Chengyu Hu; Lingbao Kong; Meifeng Li (Fish & Shellfish Immunology, 2026)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Immunotoxicity and effects of gut microbiota in chicks exposed to low doses of deoxynivalenol and 15-acetyl-deoxynivalenol - Wandi Bu; Xinyao Wu; Zhihang Zhong; Yaping Fang; Shuang Chen; Jun Jiang; Yiqun Deng (Toxicology and Applied Pharmacology, 2025)

Phosphoenolpyruvate carboxykinase 2 (PCK2) attenuates bovine adipocyte lipolysis through PNPLA2 activity repression - Chao Jiang; Hao Wu; Jiupan Zhang; Yaping Song; Xiaoyu Song; Ruopu Jiao; Sayed Haidar Abbas Raza; Sameer Dinkar Pant; Linsen Zan; Dawei Wei (Functional & Integrative Genomics, 2025)

Retraction Note: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2025)

A framework for the dynamic identification of drought propensity: The predictive role of energy changes in drought events - Bohua Wu; Ziqi Yan; Denghua Yan; Yaping Cheng (Atmospheric Research, 2025)

Bioreduction-assisted synthesis of Co nanoclusters for selective singlet oxygen generation in ciprofloxacin degradation - Yuning Fan; Wenqian Zhang; Yaping Geng; Jiangjun Lin; Yefei Su; Kai Teng; Jiajie wu; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Research progress on properties and applications of triboelectric nanogenerators based on cellulosic triboelectric aerogels - Yuhang Qiu; Yakun Mou; Xunxiao Wu; Yaping Zeng; Yanniu Xu; Mingyang Li; Dengjun Lu (Chemical Engineering Journal, 2025)

Global Non-site Regional Visibility Seasonal Forecast Integrating Geographical Distance - Shuaiwen Wu; Siyu Chen; Yaping Shao; Yue Zhang; Wenhan Li; Shasha Qiao (Aerosol Science and Engineering, 2025)

K-doped LaAlO3 A-sites: Regulating surface basicity and oxygen species composition for highly efficient organosulfur hydrolysis - Jian Gao; Yu Zhou; Bingran Wang; Wenxuan Luo; Peng Wu; Kai Shen; Yaping Zhang (Journal of Cleaner Production, 2025)

Yield variation in early-maturing cotton in response to sowing dates and growing seasons is associated with differential resource utilization - Yadi Mi; Yaru Wang; Fengqi Wu; Yingchun Han; Beifang Yang; Yaping Lei; Shiwu Xiong; Xiaoyu Zhi; Yabing Li (European Journal of Agronomy, 2025)

Eutrophication mitigates Cu-induced inhibition on growth and photosynthetic performance in the marine diatom Thalassiosira weissflogii - Shumin Zeng; Xiangyu Li; Linrong Peng; Juntian Xu; Zhenzhen Li; Yaping Wu (Marine Pollution Bulletin, 2025)

Multi-scale quantification and optimization of spatial resilience under industrial activities: A case study of resource-based cities in China - Yaping Zhang; Jianjun Zhang; Edward Randal; Ke Wang; Xia Wu; Philippa Howden-Chapman (Sustainable Cities and Society, 2025)

Boosting arsenic removal with metastable Fe2+/Mn3+ redox process in MnFe2O4/rGO composites for high capacity and stability - Tao Zhang; Shengjia Ma; Du Chen; Qingsheng Wu; LiKun Pan; Jiang Xu; Yaping Zhao (Journal of Hazardous Materials, 2025)

Development and research progress of microalgae as a production platform for antimicrobial peptides - Qiaolei Wang; Yuyang Ma; Fengjie Sun; Kang Wang; Jinju Ma; Bingkui Zhu; Kai Cao; Yaping Shao; Yulin Cui; Hao Zhang; Yuyong Wu; Chunxiao Meng; et al. (Journal of Applied Phycology, 2025)

Deep learning-based inversion framework for fractured media characterization by assimilating hydraulic tomography and thermal tracer tomography data: Numerical and field study - Cihai Chen; Yaping Deng; Jiazhong Qian; Haichun Ma; Lei Ma; Jichun Wu; Hui Wu (Engineering Geology, 2025)

Biodetoxification of both AFB1 and ZEN by Bacillus subtilis ZJ-2019–1 in gastrointestinal environment and in mice - Jianwen Wu; Wei An; Zhenlong Wang; Boquan Gao; Jiaxue Wang; Ya Zhao; Bing Han; Hui Tao; Yaping Guo; Jinquan Wang; Xiumin Wang (Mycotoxin Research, 2025)

Dynamic simulation of local acceptance of NIMBY facilities based on the RAS-Deffuant model: The influence of government and media information - Xin Wan; Rubing Wang; Xiaoyu Dong; Jiayue Wu; Yaping Zheng; Qian Li (Environmental Impact Assessment Review, 2025)

Comparative analysis of Seabuckthorn and its significant component in enhancing fish mucosal immunity - Yuhang Liu; Lian Su; Danying Cao; Nan Wu; Yuhang Hu; Fatima Altaf; Jialin Li; Qingsong Zhu; Junheng Liu; Qianqian Zhang; Haokun Liu; Yingyin Cheng; et al. (Aquaculture, 2025)

Seismic geomorphology and reservoir conditions of a Middle Miocene submarine channel system in the Taranaki basin, New Zealand - Guangxu Wang; Wei Wu; Quan Li; Weiqing Liu; Yongsheng Zhou; Shiqin Liang; Yaping Sui (Marine and Petroleum Geology, 2025)

Joint Lamé constants and P-wave anisotropic parameter estimation of vertical transverse isotropy coal-measure gas reservoir - Haibo Wu; Yaping Huang; Yanhui Huang; Ze Bai; Jian Lei (Journal of Applied Geophysics, 2025)

A hybrid mechanism-based and data-driven model for efficient indoor temperature distribution prediction with transfer learning - Yaping Liu; Jiang Wu; Zhanbo Xu; Yuanjun Shen; Xiaohong Guan (Energy and Buildings, 2025)

High lead-tolerant mutant Bacillus tropicus AT31-1 from rhizosphere soil of Pu-erh and its remediation mechanism - Qiang Li; Wenxia Yuan; Xiujuan Deng; Yaping Chen; Limei Li; Lijiao Chen; Raoqiong Che; Wei Huang; Yamin Wu; Chun Wang; Zejun Wang; Miao Zhou; et al. (Bioresource Technology, 2025)

Global patterns of lake microplastic pollution: Insights from regional human development levels - Dan Chen; Ping Wang; Shiqi Liu; Rui Wang; Yaping Wu; A-Xing Zhu; Chunnuan Deng (Science of The Total Environment, 2024)

The alleviating effects and mechanisms of Lactiplantibacillus plantarum MC14 on hyperuricemia in mice - Jie Xiong; Jia-Juan Wu; Dong-mei Liu; Muhammad Yousaf; Liu-Jun Liu; Suping Zeng; Qinqin Li; Jun Tang; Yaping Wu (Food Bioscience, 2024)

Sinensetin from citrus peel alleviates DSS-induced inflammation by regulating gut microbiota and serum metabolism in mice - Zuomin Hu; Zhongxing Chu; Xuke Ling; Yuchi Wu; Dandan Qin; Feiyan Yang; Xudong Yu; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

Effects of LAZY family genes on shoot gravitropism in Lotus japonicus - Shaoming Xu; Shusi Song; Huawu Jiang; Guojiang Wu; Yaping Chen (Plant Science, 2024)

Rill erosion and controlling factors on highway side-slopes in the permafrost region - Rui Li; Lilei Wu; Longxi Cao; Yaping Kong; Guo Chen; Ting Wu (Journal of Mountain Science, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

Assessment of uric acid-lowering activity, safety and stress tolerance of Lactiplantibacillus plantarum MC14 based on whole gene sequencing and phenotyping experiments - Jie Xiong; Lingxing Feng; Muhammad Yousaf; Suping Zeng; Jun Tang; Yaping Wu; Qinqin Li; Dong-mei Liu (Food Bioscience, 2024)

Mechanism of probiotics in the intervention of colorectal cancer: a review - Qinqin Li; Dongmei Liu; Minghua Liang; Yichao Zhu; Muhammad Yousaf; Yaping Wu (World Journal of Microbiology and Biotechnology, 2024)

Electroacupuncture Ameliorates Neuronal Damage and Neurological Deficits after Cerebral Ischemia-Reperfusion Injury via Restoring Telomerase Reverse Transcriptase - Dan Chen; Yunxia Xiang; Di Wu; Hui Wang; Yaping Huang; Hongbo Xiao (Cell Biochemistry and Biophysics, 2024)

Effect of maternal cigarette smoke exposure on COPD progression in offspring mice - Jiawei Sun; Huan Chen; Xu Xu; Yaping Dou; Baofa Wu; Hongyang Zhang; Song Shang; Wuzhuang Sun (Reproductive Toxicology, 2024)

Carrier effects of face mask-derived microplastics on metal ions: Enhanced adsorption by photoaging combined with biofilms, exemplified with Pb(Ⅱ) - Shuai Tang; Shengjia Ma; Lujian Lin; Yimei Ding; Xiaoting Zhang; Xiaowei Wu; Qun Zhang; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Seasonal dynamics, tidal influences, and anthropogenic impacts on microplastic distribution in the Yangtze River estuary: A comprehensive characterization and comparative analysis - Panfeng Wu; Yuchuan Fan; Xinxin Zhang; Wei Wu; Zaifeng Zhang; Yaping Wu; Jingyi Wang; Jing Xu; Tianming Chen; Bin Gao (Journal of Hazardous Materials, 2024)

Fabric structure and polymer composition as key contributors to micro(nano)plastic contamination in face masks - Shuai Tang; Qun Zhang; Haowen Xu; Mengyuan Zhu; Md. Nahid Pervez; Bing Wu; Yaping Zhao (Journal of Hazardous Materials, 2024)

Machine learning framework develops neutrophil extracellular traps model for clinical outcome and immunotherapy response in lung adenocarcinoma - A. Xuan Han; B. Yaping Long; C. Yao Li; D. Di Huang; E. Qi Xiong; F. Jinfeng Li; G. Liangliang Wu; Qiaowei Liu; G. Bo Yang; H. Yi Hu (Apoptosis, 2024)

Recalcitrant components accumulation in dissolved organic matter decreases microbial metabolic quotient of red soil under long-term manuring - Xiao Yang; Shuai Zhang; Dong Wu; Yaping Huang; Lu Zhang; Kailou Liu; Huiqiao Wu; Shengli Guo; Wenju Zhang (Science of The Total Environment, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Recycling of spent lithium-ion batteries into SO2‑tolerant low temperature NH3-SCR catalyst - Na Wu; Qiao Zhang; Wenli Wang; Gang Xue; Yaping Wang; Cairong Gong (Journal of Environmental Chemical Engineering, 2024)

Effect of complex prebiotics on Lactobacillus gasseri JM1 fermented soymilk: Physicochemical, flavor characteristics, and metabolites - Yaping Zheng; Wenfang Wu; Man Zhu; Yilin Sun; Dong Hu; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Bioscience, 2024)

Novel long-span cable-stayed deck arch bridge: Concept and structural characteristics - Yaping Lai; Yanzi Wu; Guannan Wang (Engineering Structures, 2024)

Revelation of HCl poisoning and enhancement mechanism on N-modified Al2O3 catalysts for COS and CS2 hydrolysis - Peng Wu; Yaping Zhang; Yun Xu; Bingran Wang; Kai Shen; Ke Zhuang; Sheng Wang; Shule Zhang; Shipeng Ding (Fuel, 2024)

Development of food-grade xylanase encapsulation using electrospray dextran microparticles - Yaping Zhang; Chun Liu; Yingjie Lin; Hong Wu; Ying Lin; Fengguang Zhao; Shuangyan Han (Food Hydrocolloids, 2024)

An Advanced Molecularly Imprinted Photochemical Sensor Based Carbon Quantum dots for Highly Sensitive Detection of Chloramphenicol in Food - Hao Liu; Jing Yang; Xuyuan Sun; Peijie Wu; Guan Wang; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2024)

Nitrogen-doping boosted the activity of K/Al2O3 catalysts in simultaneous removal of COS and CS2: An experimental and theoretical study - Peng Wu; Shipeng Ding; Bingran Wang; Kai Shen; Shule Zhang; Yaping Zhang (Journal of Environmental Chemical Engineering, 2024)

Long-term liming mitigates the positive responses of soil carbon mineralization to warming and labile carbon input - Qiong Xiao; Wenju Zhang; Lei Wu; Yaping Huang; Zejiang Cai; Dongchu Li; Xingliang Xu; Iain P. Hartley (Journal of Environmental Management, 2024)

Establishment of an efficient callus transient transformation system for Vitis vinifera cv. ‘Chardonnay’ - Jieping Wu; Junxia Zhang; Xinyi Hao; Kai Lv; Yaping Xie; Weirong Xu (Protoplasma, 2024)

Geographic information system-based multi-criteria decision-making analysis for investment assessment of wind-photovoltaic-shared energy storage power stations: a case study of Shanxi Province - Yaping Wang; Jianwei Gao; Lingli Wei; Haoyu Wu; Shutong Zhao (Environmental Science and Pollution Research, 2024)

Sinomenine improves resistance to foodborne enteritis and Anti-bacteria mucosal immunity in grass carp - Yuhang Liu; Danying Cao; Nan Wu; Xuyang Zhao; Qingsong Zhu; Lian Su; Fatima Altaf; Qianqian Zhang; Haokun Liu; Yongming Li; Bruno Hamish Unger; Yingyin Cheng; et al. (Aquaculture, 2024)

The miR-34b/MEK/ERK pathway is regulated by NR5A1 and promotes differentiation in primary bovine Sertoli cells - Qibing Tao; Linlin Zhang; Yun Zhang; Mingming Liu; Jie Wang; Qian Zhang; Jiancheng Wu; Aihua Wang; Yaping Jin; Keqiong Tang (Theriogenology, 2024)

Different ligand functionalized bimetallic (Zr/Ce)UiO-66 as a support for immobilization of phosphotungstic acid with enhanced activity for the esterification of fatty acids - Qiuyun Zhang; Yaping Wu; Xingyue Hong; Zhenying Li; Yanting Lei; Rongfei Yu; Taoli Deng; Yutao Zhang; Peihua Ma (Sustainable Chemistry and Pharmacy, 2024)

An approach to complex transboundary water management in Central Asia: Evolutionary cooperation in transboundary basins under the water-energy-food-ecosystem nexus - Lidan Guo; Yueting Wu; Feng Huang; Peiran Jing; Yaping Huang (Journal of Environmental Management, 2024)

Study on the effect of cyclic catalytic pyrolysis on sludge pyrolysis products - Yan Wu; Yuexin Zhang; Maoqing Wang; Yaping Xia; Guoxin Lan; Bin Yan; Yue Yu; Xinyi Xiong; Junhan Zou; Yin Zhu (Journal of Environmental Chemical Engineering, 2024)

Before dinner: The health value of gaseous fuels - Yaping Luo; Jianxian Wu (Energy Policy, 2024)

Recovery and reuse of spent lithium-ion batteries as catalysts for low-temperature NH3-SCR - Na Wu; Mengtao Li; Qiao Zhang; Gang Xue; Yaping Wang; Cairong Gong (Chemical Engineering Journal, 2024)

RETRACTED ARTICLE: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2024)

Gallic acid acts as an anti-inflammatory agent via PPARγ-mediated immunomodulation and antioxidation in fish gut-liver axis - Xuyang Zhao; Lei Zhang; Nan Wu; Yuhang Liu; Jiayuan Xie; Lian Su; Qingsong Zhu; Bruno Hamish Unger; Fatima Altaf; Yuhang Hu; Weidong Ye; Zhixian Qiao; et al. (Aquaculture, 2024)

Long-term manuring facilitates glomalin-related soil proteins accumulation by chemical composition shifts and macro-aggregation formation - Hongbo Yang; Qiong Xiao; Yaping Huang; Zejiang Cai; Dongchu Li; Lei Wu; Jeroen Meersmans; Gilles Colinet; Wenju Zhang (Soil and Tillage Research, 2024)

Functional characterization of polyol/monosaccharide transporter 1 in Lotus japonicus - Leru Liu; Shaoming Xu; Lu Tian; Xuelian Qin; Guojiang Wu; Huawu Jiang; Yaping Chen (Journal of Plant Physiology, 2024)

An assessment of natural and anthropogenic influences on atmospheric fluoride deposition in central Tibetan Plateau during 1951–2008 A.D. using the Zangser Kangri ice core - Xiang Zou; Wangbin Zhang; Shuangye Wu; Jinhai Yu; Jing Song; Hongxi Pang; Yaping Liu; Shugui Hou (Atmospheric Environment, 2024)

Superior solar water purification achieved by the excellent photothermal conversion and thermal management of porous plasmonic TiN nanoparticles - Yaping Gao; Xiaojie Zhou; Nuo Fu; Sihua Su; Baopeng Ma; Qifeng Ruan; Di Wu; Nan Zhang; Ziwei Deng; Ruibin Jiang (Chemical Engineering Journal, 2023)

Study on the seepage mechanisms of rock with bifurcation fractures under confining pressure - Haichun Ma; Peichao Feng; Jiazhong Qian; Yaping Deng; Daoxiang Wu (Hydrogeology Journal, 2023)

Neoproterozoic subduction-related active rifting in the South China Craton: insights from geochemical and zircon Hf isotopic data - Weizhen Tian; Guanghui Wu; Yaping Wang; Yang Shuai; R. Damian Nance; Xiaojun Zhou; Hakro Ahmed Suhail; Chen Zhang; Bo Zheng (International Geology Review, 2023)

Enhancing efficiency of biological contact oxidation reactors through filaments optimization of basalt fibers bio-carriers: Insights from a pilot-scale study - Huicheng Ni; Muhammad Arslan; Tiancai Zhang; Lizhuang Chen; Yaping Wang; Junchao Qian; Fu Cao; Zhiren Wu; Mohamed Gamal El-Din (Journal of Water Process Engineering, 2023)

Clean removal of silicon (IV) and vanadium (V) from high concentration chromium (VI) solutions in the chromate production processes - Xinqian Li; Bo Li; Yaping Dong; Zhengrong Niu; Dandan Gao; Haitao Feng; Wu Li (Journal of Cleaner Production, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Soybean phenological changes in response to climate warming in three northeastern provinces of China - Minghua Xin; Zhenggui Zhang; Yingchun Han; Lu Feng; Yaping Lei; Xiaofei Li; Fengqi Wu; Jian Wang; Zhanbiao Wang; Yabing Li (Field Crops Research, 2023)

Characterization of DNAPL source zones in clay-sand media via joint inversion of DC resistivity, induced polarization and borehole data - Xueyuan Kang; Christopher Power; Amalia Kokkinaki; André Revil; Jichun Wu; Xiaoqing Shi; Yaping Deng (Journal of Contaminant Hydrology, 2023)

How does digitalization drive carbon emissions? The inverted U-shaped effect in China - Ruijing Zheng; Ge Wu; Yu Cheng; Haimeng Liu; Yaping Wang; Xinyang Wang (Environmental Impact Assessment Review, 2023)

Au loaded mesoporous SiO2/gelatin hydrogel: Detecting low humidity and NH3 - Zhiyan Ma; Yunlong Yu; Ke Wu; Yaping Song; Sen Liu; Xi Yang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2023)

Sodium acetate trihydrate/melamine foam composite PCM encapsulated by CuS/rGO modified epoxy resin and endowed with light-to-heat conversion properties - Henghua Zhang; Qianbin Dong; Yaping Tang; Jialing Wu; Wenjian Bi; Yue Gao; Jiabang Wang; Hui Yang (Chemical Engineering Journal, 2023)

Visualize intracellular β-galactosidase using an asymmetric near-infrared fluorescent probe with a large Stokes shift - Shijun Chen; Xiaodong Ma; Haijie Wang; Lin Wang; Yuanyuan Wu; Yaping Wang; Yiyi Li; Wenkang Fan; Caoyuan Niu; Shicong Hou (Analytica Chimica Acta, 2023)

Improved activity and significant SO2 tolerance of Sb–Pd–V oxides on N-doped TiO2 for CB/NO synergistic degradation - Guobo Li; Yaping Zhang; Peng Wu; Kai Shen; Shule Zhang; Shipeng Ding (Chemosphere, 2023)

Rare earth element recovery and aluminum-rich residue production from high alumina fly ash by alkali pre-desilication enhance the mechanochemical extraction process - Mingfei Xing; Xiaofang Wu; Zixin Li; Fan Zhang; Yaping Wang; Li Zhao (Process Safety and Environmental Protection, 2023)

Optimizing plant type structure to adjust the temporal and spatial distribution of water consumption and promote the growth and yield formation of cotton - Yaru Wang; Jiale Chen; Fengqi Wu; Beifang Yang; Yingchun Han; Lu Feng; Zhanbiao Wang; Xiaofei Li; Yaping Lei; Shiwu Xiong; Guoping Wang; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

In situ confined growth of g-C3N4/pigment compound catalyst in porous diatomite for enhancing photocatalytic nicotine elimination and bacterial inactivation - Junting Gao; Zhijing Wu; Yaping Wang; Yunjin Zhong; Feng Gao; Wenxing Chen; Wangyang Lu (Journal of Environmental Chemical Engineering, 2023)

Design of bifunctional TiO2-SSZ-13 mixed supports for potassium-resistant vanadia catalysts for NH3-SCR - Xuesong Liu; Yaping Yang; Jiaying Li; Yang Gao; Kaihao Fan; Yanghui Wang; Xintao Xu; Letong Yang; Xiaodong Wu (Fuel, 2023)

Structural annotation, semi-quantification and toxicity prediction of pyrrolizidine alkaloids from functional food: In silico and molecular networking strategy - Yaping Xu; Jie Li; Huajian Mao; Wei You; Jia Chen; Hua Xu; Jianfeng Wu; Ying Gong; Lei Guo; Tao Liu; Wuju Li; Bin Xu; et al. (Food and Chemical Toxicology, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

Identification of nsLTP family in Chinese white pear (Pyrus bretschneideri) reveals its potential roles in russet skin formation - Jiawei Li; Qi Wang; Yajing Wang; Xinyi Wu; Yaping Liu; Minchen Wan; Lindu Wang; Xiexuan Wang; Cheng Zhang; Xueqian Wang; Xiaomei Tang; Wei Heng (Planta, 2023)

Long-term manuring enhances soil gross nitrogen mineralization and ammonium immobilization in subtropical area - Jun Wang; Lei Wu; Qiong Xiao; Yaping Huang; Kailou Liu; Yan Wu; Dongchu Li; Yinghua Duan; Wenju Zhang (Agriculture, Ecosystems & Environment, 2023)

Multi-response assessment for carbon emission and hardening effect in laser surface quenching - Jianzhao Wu; Chaoyong Zhang; Shuaikun Zhang; Yaping Ren; Hongwu Cheng; Guangdong Tian (Environmental Science and Pollution Research, 2023)

The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China - Weibin Huang; Fengqi Wu; Zhenggui Zhang; Yongming Meng; Jian Wang; Qinqin Li; Yingchun Han; Lu Feng; Xiaofei Li; Guoping Wang; Yaping Lei; Zhengyi Fan; et al. (Journal of Cleaner Production, 2023)

Origin, composition, and accumulation of dissolved organic matter in a hypersaline lake of the Qinghai-Tibet Plateau - Yaoling Zhang; Keli Yang; Hongmei Chen; Yaping Dong; Wu Li (Science of The Total Environment, 2023)

Enhanced performance and DFT study of sulfur poisoning mechanism of modified Al2O3 catalyst in COS hydrolysis - Peng Wu; Shipeng Ding; Kai Shen; Hongqiang Yang; Sheng Wang; Shule Zhang; Yaping Zhang (Fuel, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Effects of low-protein-high-starch diet on growth performance, glucose and lipid metabolism of Amur sturgeon (Acipenser schrenckii) during feeding and starvation phases - Xiaoran Zhang; Yaping Zhu; Hongcheng Wei; Xu Gu; Xiufeng Wu; Min Xue; Xiaofang Liang (Aquaculture, 2023)

Experimental study on the treatment of desulfurization wastewater from coal-fired power plant by spray evaporation - Zongkang Sun; Ning Zhao; Yongxin Feng; Fengjun Liu; Chenjian Cai; Guangmin Che; Yaping Zhang; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

How industrial water resources green efficiency varies in China: a case study of the Yangtze River Economic Belt considering unexpected output - Dalai Ma; Fengtai Zhang; Yaping Xiao; Lei Gao; Hongbo Liao; Na Zhao; Yuedong Xiao; Xingyu Yang; Wenli Wu (Environment, Development and Sustainability, 2022)

Gene expression in the microbial consortia of colonial Microcystis aeruginosa ‐a potential buoyant particulate biofilm - Limei Shi; Yuanfeng Cai; Shengling Gao; Daoyan Fang; Yaping Lu; Pengfu Li; Qinglong L. Wu (Environmental Microbiology, 2022)
Microcystis spp., notorious bloom‐forming cyanobacteria, are often present in colony form in eutrophic lakes worldwide. Uncovering the mechanisms underlying Microcystis colony formation and maintenance is vital to controlling the blooms, but it has long been a challenge. Here, bacterial communities and gene expression patterns of colonial and unicellular forms of one non‐axenic strain of Microcystis aeruginosa isolated from Lake Taihu were compared. Evidently, different microbial communities between them were observed through 16S rDNA MiSeq sequencing. Metatranscriptome analyses revealed that transcripts for pathways involved in bacterial biofilm formation, such as biosynthesis of peptidoglycan and arginine by Bacteroidetes , methionine biosynthesis, alginate metabolism, flagellum, and motility, as well as widespread colonization islands by Proteobacteria , were highly enriched in the colonial form. Furthermore, transcripts for nitrogen fixation and denitrification pathways by Proteobacteria that usually occur in biofilms were significantly enriched in the colonial Microcystis . Results revealed that microbes associated with Microcystis colonies play important roles through regulation of biofilm‐related genes in colony formation and maintenance. Moreover, Microcystis colony represents a potential ‘buoyant particulate biofilm’, which is a good model for biofilm studies. The biofilm features of colonial Microcystis throw a new light on management and control of the ubiquitous blooms in eutrophic waters.

Changes in Transcriptome and Ultrastructure Reveal Salinity Tolerance of Obscure Puffer Takifugu obscurus - Jun Wang; Xuexia Zhu; Yunfei Sun; Lei Gu; Yaping Wu; Yafen Chen; Zhou Yang (Frontiers in Marine Science, 2022)
Fish can maintain a stable intracellular concentration of ions in environments of variable salinities through osmoregulation. In this study, we focused on obscure puffer Takifugu obscurus ( T. obscurus ), an anadromous fish with high commercial value and rapid depression of wide populations, to investigate changes at molecular and physiological levels underlying salinity tolerance through multifaceted analyses integrating transcriptomics and micrography. We found that with the increase of salinity, the structure of the three main osmoregulation organs, i.e., gill, intestine, and kidney had remarkable changes. The results of transcriptome demonstrated that the ATP-binding box transporter and cyclic adenosine monophosphate (cAMP) signaling pathway in the gill and kidney were significantly reduced. Growth hormone, prolactin, and cortisol regulated more transporters of body composition and stimulated chloride cell proliferation and differentiation, which change the capacity for membrane transport between ion and water molecules. Adenosine-activating protein kinase and thyroid hormone signaling pathway were also significantly upregulated. These transcriptional levels changes of T. obscurus combined with ultrastructure in response to salinity increase indicated that osmoregulation is a complex process involving multiple organs and signaling pathways. Overall, this study can deepen the understanding of osmotic regulation during fish migration.

Chemical composition and Pb(II) binding of dissolved organic matter in a hypersaline lake in China - Keli Yang; Yaoling Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Conversion of organics and minerals into electricity and microalgae using a dual-membrane cylinder photo-microbial fuel cell - Gang Li; Haixing Chang; Yajun Zou; Jianzhi Yue; Yaping Zheng; Haowen Feng; Haihua Wu; Wenbo Wu; Jie Lou; Xueqiang Qi; Xingran Zhang (Environmental Chemistry Letters, 2021)

Long-term manuring increases microbial carbon use efficiency and mitigates priming effect via alleviated soil acidification and resource limitation - Qiong Xiao; Yaping Huang; Lei Wu; Yanfang Tian; Qiqi Wang; Boren Wang; Minggang Xu; Wenju Zhang (Biology and Fertility of Soils, 2021)

The inhibitory effects of the antifouling compound Irgarol 1051 on the marine diatom Skeletonema sp. across a broad range of photosynthetically active radiation - Yao Tang; Cheng Chen; Yangjie Sheng; Peijian Ding; Xinyu Wu; John Beardall; Yaping Wu (Environmental Science and Pollution Research, 2021)

Pseudomonas aeruginosa outer membrane vesicles ameliorates lung ischemia–reperfusion injury by regulating the balance of regulatory T cells and Th17 cells through Tim-3 and TLR4/NF-κB pathway - Bo Liu; Fengxia Ding; Ding Cao; Jiang Liu; Yaping Wang; Chun Wu (Inflammation Research, 2021)

Exosomes derived from astrocytes after oxygen-glucose deprivation promote differentiation and migration of oligodendrocyte precursor cells in vitro - Yaping Xu; Yeye Tian; Yao Wang; Li Xu; Guini Song; Qiao Wu; Wei Wang; Minjie Xie (Molecular Biology Reports, 2021)

Conditional Deletion of Foxg1 Alleviates Demyelination and Facilitates Remyelination via the Wnt Signaling Pathway in Cuprizone-Induced Demyelinated Mice - Fuxing Dong; Dajin Liu; Feiyu Jiang; Yaping Liu; Xiuxiang Wu; Xuebin Qu; Jing Liu; Yan Chen; Hongbin Fan; Ruiqin Yao (Neuroscience Bulletin, 2021)
The massive loss of oligodendrocytes caused by various pathological factors is a basic feature of many demyelinating diseases of the central nervous system (CNS). Based on a variety of studies, it is now well established that impairment of oligodendrocyte precursor cells (OPCs) to differentiate and remyelinate axons is a vital event in the failed treatment of demyelinating diseases. Recent evidence suggests that Foxg1 is essential for the proliferation of certain precursors and inhibits premature neurogenesis during brain development. To date, very little attention has been paid to the role of Foxg1 in the proliferation and differentiation of OPCs in demyelinating diseases of the CNS. Here, for the first time, we examined the effects of Foxg1 on demyelination and remyelination in the brain using a cuprizone (CPZ)-induced mouse model. In this work, 7-week-old Foxg1 conditional knockout and wild-type (WT) mice were fed a diet containing 0.2% CPZ w/w for 5 weeks, after which CPZ was withdrawn to enable remyelination. Our results demonstrated that, compared with WT mice, Foxg1 -knockout mice exhibited not only alleviated demyelination but also accelerated remyelination of the demyelinated corpus callosum. Furthermore, we found that Foxg1 knockout decreased the proliferation of OPCs and accelerated their differentiation into mature oligodendrocytes both in vivo and in vitro . Wnt signaling plays a critical role in development and in a variety of diseases. GSK-3β, a key regulatory kinase in the Wnt pathway, regulates the ability of β-catenin to enter nuclei, where it activates the expression of Wnt target genes. We then used SB216763, a selective inhibitor of GSK-3β activity, to further demonstrate the regulatory mechanism by which Foxg1 affects OPCs in vitro . The results showed that SB216763 clearly inhibited the expression of GSK-3β, which abolished the effect of the proliferation and differentiation of OPCs caused by the knockdown of Foxg1 . These results suggest that Foxg1 is involved in the proliferation and differentiation of OPCs through the Wnt signaling pathway. The present experimental results are some of the first to suggest that Foxg1 is a new therapeutic target for the treatment of demyelinating diseases of the CNS.

Transcriptomic analysis reveals somatic embryogenesis-associated signaling pathways and gene expression regulation in maize (Zea mays L.) - Meiqi Ding; Haixiao Dong; Yingjie Xue; Shengzhong Su; Ying Wu; Shipeng Li; Hongkui Liu; He Li; Junyou Han; Xiaohui Shan; Yaping Yuan (Plant Molecular Biology, 2020)

Could urinary ACE2 protein level help identify individuals susceptible to SARS-CoV-2 infection and complication? - Xiaotian Ni; Changqing Sun; Yaping Tian; Yanjie Huang; Tongqing Gong; Lan Song; Xing Yang; Kai Li; Nairen Zheng; Jianping Wang; Hongxing Wu; Ruoxian Zhang; et al. (Science China Life Sciences, 2020)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Improved activity of Ho-modified Mn/Ti catalysts for the selective catalytic reduction of NO with NH3 - Yaping Zhang; Peng Wu; Guobo Li; Ke Zhuang; Kai Shen; Sheng Wang; Tianjiao Huang (Environmental Science and Pollution Research, 2020)

Solar UV radiation exacerbates photoinhibition of a diatom by antifouling agents Irgarol 1051 and diuron - Rui Hou; Yaping Wu; Juntian Xu; Kunshan Gao (Journal of Applied Phycology, 2020)

Application of next-generation sequencing to screen for pathogenic mutations in 123 unrelated Chinese patients with Marfan syndrome or a related disease - Jiacheng Li; Chaoxia Lu; Wei Wu; Yaping Liu; Rongrong Wang; Nuo Si; Xiaolu Meng; Shuyang Zhang; Xue Zhang (Science China Life Sciences, 2019)

Identification of Potential Biomarkers with Diagnostic Value in Pituitary Adenomas Using Prediction Analysis for Microarrays Method - Hu Peng; Yue Deng; Longhao Wang; Yin Cheng; Yaping Xu; Jianchun Liao; Hao Wu (Journal of Molecular Neuroscience, 2019)

Laboratory experiments demonstrate that the hissing of the Chinese alligator can effectively inhibit movement of flower fish Ptychobarbus kaznakovi - Guoyong Liu; Yujiao Wu; Xiujun Shen; Yaping Hu; XiHuo Qin; Weixin Tian; Liming Liu; Xiaoling Wang; Xiaotao Shi (Hydrobiologia, 2019)

Brittleness index analysis of coal samples - Haibo Wu; Pingsong Zhang; Shouhua Dong; Yaping Huang; Min Zhang (Acta Geophysica, 2019)

The Resveratrol Alleviates the Hepatic Toxicity of CuSO4 in the Rat - Yaping Tian; Bing Wu; Xiaoping Li; Xuefei Jin; Fuqiang Zhang; Chunyan Jiang; Wenzhou Xu; Hang Li; Heyuan Wang (Biological Trace Element Research, 2019)

Delineation of contaminant plume for an inorganic contaminated site using electrical resistivity tomography: comparison with direct-push technique - Qing Liao; Yaping Deng; Xiaoqing Shi; Yuanyuan Sun; Weidong Duan; Jichun Wu (Environmental Monitoring and Assessment, 2018)

Chemical characterization of fractions of dissolved humic substances from a marginal sea—a case from the Southern Yellow Sea - Yaoling Zhang; Keli Yang; Jinzhou Du; Fenfen Zhang; Yaping Dong; Wu Li (Journal of Oceanology and Limnology, 2018)

Evaluation of CBM reservoir fracture characteristics by azimuthal AVA inversion - Yiming Zhuang; Shouhua Dong; Haibo Wu; Yaping Huang (Arabian Journal of Geosciences, 2017)

Novel rice mutants overexpressing the brassinosteroid catabolic gene CYP734A4 - Wenjing Qian; Chao Wu; Yaping Fu; Guocheng Hu; Zhengquan He; Wenzhen Liu (Plant Molecular Biology, 2017)

Environmental filtering decreases with fish development for the assembly of gut microbiota - Qingyun Yan; Jinjin Li; Yuhe Yu; Jianjun Wang; Zhili He; Joy D. Van Nostrand; Megan L. Kempher; Liyou Wu; Yaping Wang; Lanjie Liao; Xinghao Li; Shu Wu; et al. (Environmental Microbiology, 2016)
Summary Gut microbiota typically occupy habitats with definable limits/borders that are comparable to oceanic islands. The gut therefore can be regarded as an ‘island’ for the assembly of microbial communities within the ‘sea’ of surrounding environments. This study aims to reveal the ecological mechanisms that govern microbiota in the fish gut ‘island’ ecosystem. Taxonomic compositions, phylogenetic diversity, and community turnover across host development were analyzed via the high‐throughput sequencing of 16S rRNA gene amplicons. The results indicate that the Shannon diversity of gut microbiota in the three examined freshwater fish species all significantly decreased with host development, and the dominant bacterial taxa also changed significantly during host development. Null model and phylogenetic‐based mean nearest taxon distance (MNTD) analyses suggest that host gut environmental filtering led to the assembly of microbial communities in the fish gut ‘island’. However, the phylogenetic clustering of local communities and deterministic processes that governed community turnover became less distinct as the fish developed. The observed mechanisms that shaped fish gut microbiota seemed to be mainly shaped by the gut environment and by some other selective changes accompanying the host development process. These findings greatly enhance our understanding of stage‐specific community assembly patterns in the fish gut ecosystem.

Genome-wide analysis of the terpene synthase gene family in physic nut (Jatropha curcas L.) and functional identification of six terpene synthases - Wangdan Xiong; Pingzhi Wu; Yongxia Jia; Xiaoyi Wei; Liangxiong Xu; Yanfang Yang; Deyou Qiu; Yaping Chen; Meiru Li; Huawu Jiang; Guojiang Wu (Tree Genetics & Genomes, 2016)

Tissue expression analysis, cloning and characterization of the 5′-regulatory region of the bovine FABP3 gene - Anning Li; Lijuan Wu; Xiaoyu Wang; Yaping Xin; Linsen Zan (Molecular Biology Reports, 2016)

Isolation and functional characterization of a cold responsive phosphatidylinositol transfer-associated protein, ZmSEC14p, from maize (Zea may L.) - Xiaoyu Wang; Xiaohui Shan; Chunmei Xue; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yuan Jiang; Yanfei Zhang; Yaping Yuan (Plant Cell Reports, 2016)

Turbidity maximum formation and its seasonal variations in the Zhujiang (Pearl River) Estuary, southern China - Runqi Liu; Yaping Wang; Jianhua Gao; Ziyin Wu; Weibing Guan (Acta Oceanologica Sinica, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

DNA barcoding reveals commercial fraud related to yak jerky sold in China - Yunyu Wang; Kai He; Long Fan; Yushui Wang; Shifang Wu; Robert W. Murphy; Wenzhi Wang; Yaping Zhang (Science China Life Sciences, 2016)

Large centric diatoms allocate more cellular nitrogen to photosynthesis to counter slower RUBISCO turnover rates - Yaping Wu; Jennifer Jeans; David J. Suggett; Zoe V. Finkel; Douglas A. Campbell (Frontiers in Marine Science, 2014)

A polymorphism at miRNA-122-binding site in the IL-1α 3′UTR is associated with risk of epithelial ovarian cancer - Zhu Zhang; Bin Zhou; Qianqian Gao; Yuke Wu; Kui Zhang; Yan Pu; Yaping Song; Lin Zhang; Mingrong Xi (Familial Cancer, 2014)

Ocean acidification enhances the growth rate of larger diatoms - Yaping Wu; Douglas A. Campbell; Andrew J. Irwin; David J. Suggett; Zoe V. Finkel (Limnology and Oceanography, 2014)
Ocean acidification is changing the nature of inorganic carbon availability in the global oceans. Diatoms account for µ 40% of all marine primary productivity and are major contributors to the export of atmospheric carbon to the deep ocean. Larger diatoms are more likely to be stimulated by future increases in CO 2 availability as a result of their low surface area to volume ratio and lower diffusive flux of CO 2 relative to their carbon demand for growth. Here we quantify the effect of the partial pressure of carbon dioxide (P CO 2 ), at levels of 190, 380, and 750 µL L −1 , on the growth rate, photosystem II electron transport rate (ETR), and elemental composition for five diatom species ranging over five orders of magnitude in cell volume. Growth rates for all species were enhanced under 750 relative to 190 and 380 µL L −1 , with little change in ETR or elemental stoichiometries, indicating an enhanced allocation of photochemical energy to growth under elevated P CO 2 . P CO 2 enhancement of growth rates was size dependent. Under 750 vs. 190 µL L −1 partial pressures, growth rate was enhanced by µ 5% for the smaller diatom species to µ 30% for the largest species examined. The size dependence of CO 2 ‐stimulated growth enhancement indicates that ocean acidification may selectively favor an increase in the growth rates of larger vs. smaller phytoplankton species in the sea, with potentially significant consequences for carbon biochemistry.

Prognostic value of IL-27 polymorphisms and the susceptibility to epithelial ovarian cancer in a Chinese population - Zhu Zhang; Bin Zhou; Yuke Wu; Qianqian Gao; Kui Zhang; Yaping Song; Lin Zhang; Mingrong Xi (Immunogenetics, 2014)

Observational climatology and characteristics of wintertime atmospheric blocking over Ural–Siberia - Ho Nam Cheung; Wen Zhou; Yaping Shao; Wen Chen; Hing Yim Mok; Man Chi Wu (Climate Dynamics, 2013)

Comparative proteomic analysis of the H99 inbred maize (Zea mays L.) line in embryogenic and non-embryogenic callus during somatic embryogenesis - Lifang Sun; Ying Wu; Hongda Zou; Shengzhong Su; Shipeng Li; Xiaohui Shan; Jinghui Xi; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Revisiting the climatology of atmospheric blocking in the Northern Hemisphere - Ho Nam Cheung; Wen Zhou; Hing Yim Mok; Man Chi Wu; Yaping Shao (Advances in Atmospheric Sciences, 2013)

Numerical analysis for contribution of the Tibetan Plateau to dust aerosols in the atmosphere over the East Asia - Rui Mao; DaoYi Gong; YaPing Shao; GuangJian Wu; JingDong Bao (Science China Earth Sciences, 2013)

Analysis of the DNA methylation of maize (Zea mays L.) in response to cold stress based on methylation-sensitive amplified polymorphisms - Xiaohui Shan; Xiaoyu Wang; Guang Yang; Ying Wu; Shengzhong Su; Shipeng Li; Hongkui Liu; Yaping Yuan (Journal of Plant Biology, 2013)

River islands, refugia and genetic structuring in the endemic brown frog R ana kukunoris ( A nura, R anidae) of the Q inghai‐ T ibetan P lateau - Weiwei Zhou; Fang Yan; Jinzhong Fu; Shifang Wu; Robert W. Murphy; Jing Che; Yaping Zhang (Molecular Ecology, 2013)
Frequently, P leistocene climatic cycling has been found to be the diver of genetic structuring in populations, even in areas that did not have continental ice sheets, such as on the Q inghai‐ T ibetan P lateau ( QTP ). Typically, species distributed on the plateau have been hypothesized to re‐treat to south‐eastern refugia, especially during the L ast G lacial M aximum ( LGM ). We evaluated sequence variation in the mitochondrial DNA gene Cytb and the nuclear DNA gene RAG ‐1 in R ana kukunoris , a species endemic to the QTP . Two major lineages, N and S, were identified, and lineage N was further subdivided into N 1 and N 2. The geographical distribution and genealogical divergences supported the hypothesis of multiple refugia. However, major lineages and sublineages diverged prior to the LGM . Demographical expansion was detected only in lineage S and sublineage N 2. Sublineage N 1 might have survived several glacial cycles in situ and did not expand after the LGM because of the absence of suitable habitat; it survived in river islands. Genetic analysis and environment modelling suggested that the north‐eastern edge of QTP contained a major refugium for R . kukunoris . From here, lineage S dispersed southwards after the LGM . Two microrefugia in northern Q ilian M ountains greatly contributed to current level of intraspecific genetic diversity. These results were found to have important implications for the habitat conservation in N orthwest C hina.

Cyanobacteria-blooming water samples from Lake Taihu induce endoplasmic reticulum stress in liver and kidney of mice - Wendi Qin; Liuyan Yang; Xuxiang Zhang; Zongyao Zhang; Lizhi Xu; Jun Wu; Jing An; Yaping Wang (Ecotoxicology, 2012)

Differential gene expression during somatic embryogenesis in the maize (Zea mays L.) inbred line H99 - Lifang Sun; Ying Wu; Shengzhong Su; Hongkui Liu; Guang Yang; Shipeng Li; Xiaohui Shan; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Influence of Eight Unclassified Missense Variants of the MLH1 Gene on Lynch Syndrome Susceptibility - Yimei Fan; Jinyun Chen; Wei Wang; Puyuan Wu; Wenxian Zhi; Binshuang Xue; Wanfen Zhang; Yaping Wang (Biochemical Genetics, 2012)

Identification and characterisation of candidate genes involved in chilling responses in maize (Zea mays L.) - Guang Yang; Hongda Zou; Ying Wu; Hongkui Liu; Yaping Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

A diagnostic study of two heavy rainfall events in South China - Liji Wu; Yaping Shao; Andrew Y. S. Cheng (Meteorology and Atmospheric Physics, 2011)

Isolation and characterization of a rice mutant with narrow and rolled leaves - Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Shihua Cheng; Wenzhen Liu (Planta, 2010)

Synoptic characteristics of heavy rainfall events in pre-monsoon season in South China - Liji Wu; Ronghui Huang; Haiyan He; Yaping Shao; Zhiping Wen (Advances in Atmospheric Sciences, 2010)

The role of MC1R gene in buffalo coat color - YongWang Miao; GuiSheng Wu; Lei Wang; DaLin Li; ShouKun Tang; JianPing Liang; HuaMing Mao; HuaiRong Luo; YaPing Zhang (Science China Life Sciences, 2010)

Identification and characterization of HTD2: a novel gene negatively regulating tiller bud outgrowth in rice - Wenzhen Liu; Chao Wu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Weijiang Luan; Zhengquan He; Zongxiu Sun (Planta, 2009)

Identification and fine mapping of a thermo-sensitive chlorophyll deficient mutant in rice (Oryza sativa L.) - Wenzhen Liu; Yaping Fu; Guocheng Hu; Huamin Si; Li Zhu; Chao Wu; Zongxiu Sun (Planta, 2007)

Mutational analysis of the mitochondrial 12S rRNA gene in Chinese pediatric subjects with aminoglycoside-induced and non-syndromic hearing loss - Zhiyuan Li; Ronghua Li; Jianfu Chen; Zhisu Liao; Yi Zhu; Yaping Qian; Sudao Xiong; Selena Heman-Ackah; Jianbo Wu; Daniel I. Choo; Min-Xin Guan (Human Genetics, 2005)